Review of carbon nanotube nanoelectronics and macroelectronics - Che, Yuchi; Chen, Haitian; Gui, Hui; Liu, Jia; Liu, Bilu; Zhou, Chongwu (Semiconductor science and technology, 2014)
Carbon nanotubes have the potential to spur future development in electronics due to their unequalled electrical properties. In this article, we present a review on carbon nanotube-based circuits in terms of their electrical performance in two major directions: nanoelectronics and macroelectronics. In the nanoelectronics direction, we direct our discussion to the performance of aligned carbon nanotubes for digital circuits and circuits designed for radio-frequency applications. In the macroelectronics direction, we focus our attention on the performance of thin films of carbon nanotube random networks in digital circuits, display applications, and printed electronics. In the last part, we discuss the existing challenges and future directions of nanotube-based nano- and microelectronics.